Evaluación de indicadores de la calidad del suelo en áreas productoras de Brócoli (Brassica oleracea), de la Parroquia Guaytacama del cantón Latacunga en el Periodo 2019-2020. - Lema Chicaiza, Juan Eduardo (2020)
The present research aims to study the quality of the soil in the broccoli (Brassica oleracea) producing area and additionally in corn producing areas (Zea mays) located in the Guaytacama parish belonging to the province of Cotopaxi, in the study We determine the physical-chemical environmental indicators: Arsenic, Cadmium, Copper, Conductivity, Apparent density, SAR Index, Mercury, pH, Lead, Texture and Particle fraction in the same way, determining the Pesticide Residues: Diazinon, Ethyl-chlorpyrifos, Demeton , Dichlorvos, Etoprop, Malathion, Ethyl-parathion, Forate, Terbufos, Ronnel, Tetrachlorvinfos, Mevinfos, Dimethoate, Disulfoton and Methyl-Azinfos, through composite samples obtained and analyzed, according to ANNEX 2 OF BOOK VI of the unified text of the legislation secondary of the Ministry of the Environment: Environmental quality standard for soil resources and remediation criteria for contaminated soils. Through the results of the analysis obtained from the samples, it was compared with the parameters established in the regulations used, it was determined that two indicators are outside the quality values such as Conductivity with a value of 935.6 us / cm and the pH of 8.65, the parameters of the pesticides analyzed are below the values of the soil quality established in the regulations, demonstrating a low degree of contamination in the study areas, the activities that are proposed to mitigate these two indicators High is the intensification of organic matter through the crushing of waste and organic fertilizers, reduction of monoculture in the broccoli (Brassica oleracea) producing area, allowing the contribution of components that acidify the pH and decrease the salts to balance conductivity, since in these areas there is the cultivation of the same species and the commercialization of the leftover waste for animal feed Additionally, I carry out a comparative analysis of the production of broccoli (Brassica oleracea) with the production of corn (Zea mays).